KADAR FLAVONOID EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L.) BERDASARKAN VARIASI KONSENTRASI PELARUT ETANOL - Henny Nurhasnawati; Risa Supriningrum; Rusdiati Helmidanora; Margareta, Sully (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Butterfly pea (Clitoria ternatea L.) is a plant used for medicinal purposes, including therapeutic, cosmetic, nutritional, and beauty applications. Flavonoids, as secondary metabolites with diverse chemical structures in plants, perform various important functions. These functions include growth regulation, coloration, protection from UV rays, and roles in defense mechanisms and signaling systems with microorganisms. These compounds also have pharmacological effects as antidiabetics, antioxidants, and antibacterials. Solvent concentration plays an important role, as it can affect the amount of active compounds extracted from natural materials. The purpose of this study was to determine the flavonoid content in butterfly pea flower extracts using ethanol solvents at concentrations of 50%, 70%, and 95%. The results of phytochemical screening tests showed that all extracts contained secondary metabolites in the form of flavonoids. Other parameters analyzed included yield, moisture content, and flavonoid content from the three ethanol concentration variations. The yields obtained were 57.14%, 54.08%, and 40.72%, respectively, while the moisture content was 9.44 ± 2.17%, 8.99 ± 2.12%, and 7.75 ± 1.97%, respectively.The highest flavonoid content was obtained in the extract with 95% ethanol solvent at 1.2939 ± 0.0880%, followed by 70% ethanol at 0.6958 ± 0.0573%, and 50% ethanol at 0.5811 ± 0.0142%. Statistical analysis using ANOVA showed that there were differences in flavonoid content between the ethanol concentration variation groups